PENGARUH KUALITAS INFORMASI AKUNTANSI DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PENGENDALIAN INTERNAL DAN KINERJA BUMDES DI KABUPATEN KOLAKA - Wulansari R, Dyah Retno; Abdullah, Muntu; Asni, Nur (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
This study aims to analyze the influence of accounting information quality and human resource competency on the performance of Village-Owned Enterprises (BUMDes) in Kolaka Regency, both directly and through internal control as a mediating variable. This study used a quantitative approach with a survey method, where data were collected through questionnaires distributed to BUMDes managers. Data analysis used Partial Least Squares (PLS) with the assistance of SmartPLS software. The results showed that accounting information quality had a positive and significant effect on BUMDes performance, but not a significant effect on internal control, and no significant effect on performance through internal control. Human resource competency was proven to have a positive and significant effect on internal control and BUMDes performance. Furthermore, internal control has a positive and significant effect on BUMDes performance and partially mediates the effect of human resource competency on BUMDes performance. The findings of this study indicate that improved BUMDes performance is not solely determined by the quality of the accounting information system, but rather by the competence of managers and the effectiveness of the internal controls implemented. This research is expected to provide theoretical contributions to the development of BUMDes management studies and provide practical considerations for village governments and BUMDes managers in sustainably improving village business performance.